Real-life GH dosing patterns in children with GHD, TS or born SGA: a report from the NordiNet® International Outcome Study - Blankenstein, Oliver; Snajderova, Marta; Blair, Jo; Pournara, Effie; Pedersen, Birgitte Tønnes; Petit, Isabelle Oliver (European journal of endocrinology, 2017)
OBJECTIVE: To describe real-life dosing patterns in children with growth hormone deficiency (GHD), born small for gestational age (SGA) or with Turner syndrome (TS) receiving growth hormone (GH) and enrolled in the NordiNet International Outcome Study (IOS; Nbib960128) between 2006 and 2016. DESIGN: This non-interventional, multicentre study included paediatric patients diagnosed with GHD (isolated (IGHD) or multiple pituitary hormone deficiency (MPHD)), born SGA or with TS and treated according to everyday clinical practice from the Czech Republic (IGHD/MPHD/SGA/TS: n = 425/61/316/119), France (n = 1404/188/970/206), Germany (n = 2603/351/1387/411) and the UK (n = 259/60/87/35). METHODS: GH dosing was compared descriptively across countries and indications. Proportions of patients by GH dose group (low/medium/high) or GH dose change (decrease/increase/no change) during years 1 and 2 were also evaluated across countries and indications. RESULTS: In the Czech Republic, GH dosing was generally within recommended levels. In France, average GH doses were higher for patients with IGHD, MPHD and SGA than in other countries. GH doses in TS tended to be at the lower end of the recommended label range, especially in Germany and the UK; the majority of patients were in the low-dose group. A significant inverse association between baseline height standard deviation score and GH dose was shown (P < 0.05); shorter patients received higher doses. Changes in GH dose, particularly increases, were more common in the second (40%) than in the first year (25%). CONCLUSIONS: GH dosing varies considerably across countries and indications. In particular, almost half of girls with TS received GH doses below practice guidelines and label recommendations.
Keywords: Dose-Response Relationship, Drug; Cross-Sectional Studies; vztah mezi dávkou a účinkem léčiva; poruchy růstu; lidský růstový hormon; hypotrofický novorozenec; Male; výzkumná zpráva; Turnerův syndrom; mladiství; Česká republika; výsledek terapie; Human Growth Hormone; mužské pohlaví; Infant, Small for Gestational Age; Spojené království; průřezové studie; Prospective Studies; Německo; Czech Republic; hypofyzární nanismus; dítě; Follow-Up Studies; Child; Research Report; následné studie; Child, Preschool; internacionalita; Growth Disorders; ženské pohlaví; Humans; předškolní dítě; prospektivní studie; Germany; Francie; United Kingdom; France; Female; Turner Syndrome; Adolescent; Treatment Outcome; lidé; Internationality; Dwarfism, Pituitary